Simultaneous Pancreas Kidney Transplantation Improves Cardiovascular Autonomic Neuropathy with Improved Valsalva Ratio as the Most Precocious Test - María Argente-Pla; Antonia Pérez-Lázaro; Antonio Martinez-Millana; María Isabel Del Olmo-García; Jordi Espí-Reig; Isabel Beneyto-Castello; Rafael López-Andújar; Juan Francisco Merino-Torres (Journal of Diabetes Research)
Background. Simultaneous pancreas-kidney (SPK) transplantation is a proven option of treatment for patients with type 1 diabetes mellitus (T1DM) and related end-stage renal disease. There is discrepancy between the results of different studies about the impact of prolonged normalization of glucose metabolism achieved by SPK on the course of diabetic complications including severe forms of diabetic neuropathy. The objective of the study was to evaluate the prevalence of cardiovascular autonomic neuropathy (CAN) in patients undergoing SPK transplantation and its evolution 10 years after transplantation. Methods. Prospective study of 81 patients transplanted in a single center from year 2002 to 2015. Autonomic function was assessed using cardiovascular autonomic reflex tests (CARTs). CARTs were made before SPK transplantation and during the follow-up. Evolution of tests after SPK transplantation was evaluated by contrasting hypotheses (paired tests). Multiple testing was adjusted with the Benjamini-Hochberg procedure with a false discovery rate of 10%. Results. 48 males and 33 females, mean age 37.4±5.7 years, mean BMI 24.0±3.4 kg/m2, and mean duration of diabetes 25.5±6.5 years, received SPK transplantation. Ten years after SPK transplantation, 56 patients re tained the pancreatic graft (42 of them with normofunctioning pancreas and 14 with low doses of insulin therapy). These 42 patients were selected for the autonomic study. Before transplant procedure, all CART results were abnormal. After SPK transplantation, paired test analysis showed an improvement of systolic blood pressure (SBP) response to orthostasis at the 5th year after SPK (p=0.03), as well as improvement of the Valsalva ratio at the 3rd (p<0.001) and 5th (p=0.001) year after SPK. After correcting for the false discovery rate, all the variables of autonomic study reached significance at different time points. Conclusions. Prevalence of CAN in patients who are candidates for SPK transplantation is high and is generally advanced. SPK transplantation improves CAN with improved Valsalva ratio as the most precocious test.